On the nonsquare constants of L(Φ)[0,+1) - Yan, Y. Q. (Revista Matemática Complutense, 2002)
Let L(Φ)[0,+1) be the Orlicz function space generated by N−function Φ(u) with Luxemburg norm. We show the exact nonsquare constant of it when the right derivative φ(t) of Φ(u) is convex or concave.